On the Way to the Afterlife. Some Observations on the Presence of Weaponry in Early Medieval Cemeteries in the Context of Their Social and Cultural Circulation - Tomasz Kurasiński (Fasciculi Archaeologiae Historicae, 2020)
The custom of burying the dead with weaponry depended on prevailing social norms and religious beliefs which determined the choice of a particular type of weapon to be placed in a pit grave. The primary activity here seems to be the act of withdrawal of selectedelements of weaponry from further use for the purpose of including it in the posthumous equipment. This article addresses a few issues ofthis complex problem while taking account of early medieval finds, mainly from the territory of Poland. The presence of weapons in gravescould result from many ways and trajectories of their circulation, which finally contributed to a certain configuration and choice of elements of weaponry both in terms of quality as well as quantity deposited in burials. Many of the pieces of weaponry had their own special “history” or “biography” before being placed in the grave. They could have belonged to an esteemed ancestor, commemorate some special event or participate in an exchange many times.